Ultra late onset group B streptococcal sepsis with acute renal failure in a child with urethral obstruction: a case report - Freudenstein, Daniela; Reinshagen, Konrad; Petzold, Angela; Debus, Angelika; Schroten, Horst; Tenenbaum, Tobias (Journal of medical case reports, 2012)
Group B streptococci are a well-known cause of early and late onset sepsis. In neonates and older children gram-negative bacteria are mostly found in urinary tract infections and urosepsis. In adults predisposing factors for group B streptococci urinary tract infection may include diabetes mellitus and chronic renal failure.